Answers

2014-06-10T04:06:29+08:00
Let x = speed of motorcycle 
    y = speed of bicycle
    z = time for the bicycle to travel 60km

y km/hr  + 15 km/hr = x km/hr 
60 km = y km/hr * z hr
60 km = x km/hr * (z-2) hr

y + 15 = x ----->(eq 1) y = x - 15
(eq 2)60 = zy     ----->(eq 3) 60 = (x-15)z   ----> (eq 4) z = 60/(x-15)
60 = xz - 2x  -----> 60 = x (60/(x-15)) -2x

60 + 2x = 60x / (x-15)
60x - 900 + 2x^2 - 30x = 60x
2x^2 -30x -900 = 0
x^2 - 15x - 450 = 0

(x-30)(x+15) = 0
x=30km/hr

using eq 1:
y = x - 15
y = 30 - 15
y=15km/hr

using eq 2:
60 = zy
60 = z (15)
z = 4 hr

(30,15,4)
4 4 4